Selective and Efficient Transport of Silver as Ag(CN)2– Ion Using Malachite Green as Carrier - Hasani, Masoumeh (Asian Journal of Chemistry, 2016)
The facilitated transport of Ag+ from cyanide solutions through bulk liquid membrane is reported. The organic phase consisted of a chloroform solution of malachite green as carrier. The effect of pH of source phase, potassium cyanide concentration in source phase, malachite green concentration in organic phase and sodium hydroxide in receiving phase on efficiency of transport process are examined. Under optimum conditions, the extent of Ag(CN)2– transport across the liquid membrane is about 90% after 240 min. The carrier can selectively and efficiently transport ion from aqueous solutions containing other cations such as alkali and alkaline earth, Zn2+, Cd2+, Hg2+, Co2+, Ph2+, Fe2+, Ni2+ and Pd2+.